On the Variability of Chukchi Traditional Singing and Incantation Practices (Research Note) - Weinstein-Tagrina, Zoia (Études Inuit Studies, 2021)
This paper concerns the little-known, largely archaic practices of traditional Chukchi songs and incantations. Use is made of the unique Chukchi language materials of Vladimir Bogoraz, recorded by that scholar in the late 19th and early 20th centuries, as well as hitherto unknown sources from the author’s unpublished field materials, collected in Chukotka in the second half of the 20th and early 21st centuries, and here introduced into scientific circulation.